A Novel Wearable Device for Motor Recovery of Hand Function in Chronic Stroke Survivors. (July 2020) - Choudhury, Supriyo; Singh, Ravi; Shobhana, A.; Sen, Dwaipayan; Anand, Sidharth Shankar; Shubham, Shantanu; Gangopadhyay, Suparna; Baker, Mark R.; Kumar, Hrishikesh; Baker, Stuart N.
Background. In monkey, reticulospinal connections to hand and forearm muscles are spontaneously strengthened following corticospinal lesions, likely contributing to recovery of function. In healthy humans, pairing auditory clicks with electrical stimulation of a muscle induces plastic changes in motor pathways (probably including the reticulospinal tract), with features reminiscent of spike-timing dependent plasticity. In this study, we tested whether pairing clicks with muscle stimulation could improve hand function in chronic stroke survivors. Methods. Clicks were delivered via a miniature earpiece; transcutaneous electrical stimuli at motor threshold targeted forearm extensor muscles. A wearable electronic device (WD) allowed patients to receive stimulation at home while performing normal daily activities. A total of 95 patients >6 months poststroke were randomized to 3 groups: WD with shock paired 12 ms before click; WD with clicks and shocks delivered independently; standard care. Those allocated to the device used it for at least 4 h/d, every day for 4 weeks. Upper-limb function was assessed at baseline and weeks 2, 4, and 8 using the Action Research Arm Test (ARAT), which has 4 subdomains (Grasp, Grip, Pinch, and Gross). Results. Severity across the 3 groups was comparable at baseline. Only the paired stimulation group showed significant improvement in total ARAT (median baseline: 7.5; week 8: 11.5; P = .019) and the Grasp subscore (median baseline: 1; week 8: 4; P = .004). Conclusion. A wearable device delivering paired clicks and shocks over 4 weeks can produce a small but significant improvement in upper-limb function in stroke survivors.